Chemistry of the solar system - Lodders, Katharina; Fegley, Bruce (Cambridge, UK : RSC Pub., 2011)
This book is an appealing, concise, and factual account of the chemistry of the solar system. It includes basic facts about the chemical composition of the different bodies in the solar system, the major chemical processes involved in the formation of the Sun, planets, and small objects, and the chemical processes that determine their current chemical make-up. There are numerous informative summary tables and data is presented in graphical form which is useful for identifying common features of the major processes that determine the current chemical state of the planets --.
Some milestones up to the beginning of the Space Age -- The elements in the solar system -- Meteorites -- The solar nebula -- The bodies in the inner solar system -- Terrestrial atmospheric chemistry -- The greenhouse effect and biogeochemical cycles on Earth -- The outer solar system -- Appendix A. Table of abundances of nuclides in the solar system -- Appendix B. Table of average element concentrations in major chondritic meteorite groups -- Appendix C. Review of chemical kinetics.
Includes bibliographic references and index.
Keywords: Cosmochemistry; Kosmochemie; Sonnensystem; Solar system